Shear behaviour of reinforced concrete beams with small web openings. (2021) - Jabbar, Dhiaa Neama; Al-Rifaie, Ali; Hussein, Ahmed Mahdi; Shubbar, Ali A.; Nasr, Mohammed Salah; Al-Khafaji, Zainab S.
Abstract: In the current investigation, four reinforced concrete beams with square cross sectional area were poured and tested up to failure under the action of three-point loads. Three of them were designed to contain small web openings of different shapes, square, rectangular and circular while the other beam had no openings (control beam) for the purpose of comparison of findings. The load–deflection traces were successfully obtained for the tested specimens. The results indicated that perforating reinforced concrete beams with small web openings leads to a slight reduction in their ultimate loads corresponding to an increase in the ultimate deflection. Also, it was concluded that the beams with circular web openings had better shear resistance than other shapes selected here.